CASE STUDIES ON THE CURRENT SAFETY ISSUE AND WORK BEHAVIOUR OF CONSTRUCTION SITE WORKERS IN MALAYSIA - Noor Akmal Adillah Ismail; Azreen Ariff Zulkeflee; Nasruddin Faisol; Faridah Ismail (International Journal of Accounting, Finance and Business, 2020)
Vast developing countries like Malaysia are often linked to an excellent economicgrowth and rapid construction development. Therefore, the operational safety issues havealways been a hot topic in the construction sector due to the near misses and accidents are stillat an alarming rate. Although various studies and initiatives have been made to reduce theaccident rate but in reality, accidents still occur, especially at the operational level. Hence, astudy has been conducted to explore the current safety issue and work behaviour of constructionsite workers in Malaysia. This study was started out by reviewing accidents statistic reportpublished by the Department of Safety and Health (DOSH). Then, literature from varioussources mainly; journals, articles, conference papers and books were examine to strengthenthe issue. Semi structured interviews were carried out to obtain data from informants who aremainly site safety personnel who are well versed with the construction safety. The finding ofthis study reveals that near misses, incidents and accidents are still occurring at the operationallevels due to poor workers behaviours and attitudes. Despites initially, various approach suchas constant supervision, strict safety policies and regulation, implementation of safety clausesand safety training have been conducted by the management to enhance safety awarenessamong the construction workers.